Understanding Islamist terrorism in Europe: drugs, jihad and the pursuit of martyrdom - Herrington, Lewis (Routledge studies in countering violent extremism, 2022)
This book argues that guilt, shame, and remorse, associated with a history of substance abuse, explain why a minority of Islamist extremists carried out suicide terrorism in Europe between 2001 and 2018. Since 9/11, Islamist terrorism has dominated the European security landscape, but there has been little systematic analysis of either the attacks or the men responsible. This book addresses that gap, drawing on terrorist discourse, court transcripts, elite interviews, government reports, and three years of ethnography to provide an exhaustive account of how and why Islamist terrorism has occurred in Europe. Making a detailed analysis of 48 terrorist attacks carried out by 80 suicide terrorists, the book introduces two new theories. The first argues that most of these men first engaged in Islamist extremism as an alternative to substance abuse. The second contends that, following a five-stage process of radicalisation, cognitive dissonance triggered guilt, shame, and remorse over previous misconduct. From this emotional distress, suicide terrorism emerged as a rational choice ahead of either suicide or a return to active addiction. This book argues that the root cause of suicide terrorism in Europe is not so much politics or religion but is more about personal crisis and a search for redemption.